Image Quality Restoration on Historical Artifacts Using Histogram Equalization and Contrast Stretching Methods - Aidilia, Yunda; Sriani, Sriani (Newinera Publisher, 2024)
The aim of this research was to enhance the image quality of historical objects that undergo quality decline such as noise, low contrasting images, and poor sharpness. Contrast stretching and Histogram equalization are two methods of image enhancement which is used to expand and smooth out the grayscale of an image . The purpose of this study is to develop a system for enhancing the quality of images of historical heritage objects applying contrast stretching and histogram equalization techniques. Concerning the selection of the sample in this research, the data is RGB image data with a total of 10 test images in . mat file format and the process employed is in Matlab programming language The stimulation of neuron is in jpg format. The works on the contrast stretching and histogram equalization from the sample 1 to sample 10 image the results were highest on test image_citra_1 with the contrast stretching results on the base of PSNR = 32. DOS, = 61 dB and MSE = 35. 86 Db and PSNR = 19. 13 Db and MSE = 794 . 76 in histogram equalization calculations.